Attitudes Towards the Polar Regions as a Reflection of the Sense of Responsibility for the Environment. Theoretical Background for Further Study - Mamzer, Hanna; Skedsmo, Pål Wilter; Węsławski, Jan Marcin (Frontiers in Environmental Science, 2021)
The last two hundred years in the recent history of the Earth have been a period dominated by rapidly increasing human activity. Today, the discussion on the effects of anthropopressure takes the form of critical reflection on the negative impact of humanity on the natural environment. Although sparsely populated, the effects of this impact are particularly visible in the polar regions. The consequences of anthropopressure take the form of melting ice caps and glaciers, warming and thawing of permafrost, changes in sea ice structure, erosion of sea coasts, changes in the scale of Arctic fauna and flora, and a warmer climate. Research conducted in the US shows that its citizens have knowledge about polar regions, but that the level of this knowledge is low. The level of general knowledge, the level of education, and social and demographic features (age, gender, income) may influence the formation of social opinions reflected in legislative and political solutions concerning the polar regions. Social science research has already shown that changing people’s attitudes is much more effective if the process starts in adolescence, at the beginning of institutional education. In such a situation, diagnosing the attitudes of young citizens toward polar areas is important for their further development, especially if these attitudes are to be treated as a reflection of wider attitudes toward the natural environment. In this article we set forth to review how attitudes related to the polar regions, may be used as an example of general mechanisms of changing attitudes towards the environment in general. We provide analysis that can be used as background for designing empirical research and further – for designing educational and social plans promoting environmental responsibility.